ANALISIS BAURAN PEMASARAN PROMOSI DAN TEMPAT DALAM MENINGKATKAN PENJUALAN PRODUK HERBAL HPA - Kristanto Ardi; Warneri Warneri; Okianna Okianna (Universitas Tanjungpura, 2021)
AbstractTwo main marketing objectives are attracting new customers by promising superior valueand retaining current customers by providing satisfaction. The general problem that is tryingto be lifted in this research is